Electrophile induced branching cascade: a powerful approach to access various molecular scaffolds and their exploration as novel anti-mycobacterial agents - Patil, Nitin T.; Konala, Ashok; Sravanti, Sudha; Singh, Ashita; Ummanni, Ramesh; Sridhar, Balasubramanian (Chemical Communications, 2013)
Herein we report on the Electrophile Induced Branching Cascade (EIBC), a new technique to produce a variety of biologically important molecular scaffolds. Some compounds exhibit excellent activities against Mycobacterium smegmatis.

Enantioselective heterogeneous bronsted acid catalysis - Mutyala, Anil Kumar; Patil, Nitin T. (Organic Chemistry Frontiers, 2014)
This highlight describes the synthesis and catalytic activities of heterogeneous chiral Bronsted acid catalysts. The heterogeneous catalysts are stable, easily separable from the reaction mixture and can be used multiple times without any loss of activity. As a remarkable particularity, the use of heterogeneous catalyst systems has been exemplified for designing continuous flow reactors.

Enantioselective cooperative catalysis - Inamdar, Suleman M.; Shinde, Valmik S.; Patil, Nitin T. (Organic & Biomolecular Chemistry, 2015)
In recent years, enantioselective cooperative catalytic reactions, wherein two catalysts work simultaneously to form products which cannot be obtained by the use of a single catalyst alone, have attracted considerable attention. This review focuses on this emerging field, with particular emphasis on mechanistic aspects, which will help readers to understand the role of each catalyst.

Engineering ligands on the Au center: discovering broadly applicable gold catalysis with high turnover numbers - Inamdar, Suleman M.; Patil, Nitin T. (Organic Chemistry Frontiers, 2015)
The research groups of Hammond/Xu and Zhang report the discovery of new ligands for gold catalysis. With these ligands, gold catalyzed reactions have been reported for a broader range of substrates with very high TONs at a level that can match the needs of large-scale applications.

Efficient access to alkynylated quinalizinones via the gold(I)-catalyzed aminoalkynylation of alkynes - Shinde, Popat S.; Shaikh, Aslam C.; Patil, Nitin T. (Chemical Communications, 2016)
The gold-catalyzed aminoalkynylation of alkynes for the synthesis of quinalizinones is reported. For instance, the reaction of pyridinoalkynes with 1-[(triisopropylsilyl)-ethynyl]-1,2-benziodoxol-3(1H)-one (TIPS-EBX) in the presence of a catalytic amount of AuCl at 50 8C afforded alkynylated quinalizinones in 57-87% yields.

Exploiting the dual role of ethynylbenziodoxolones in gold-catalyzed C(sp)-C(sp) cross-coupling reactions - Banerjee, Somsuvra; Patil, Nitin T. (Chemical Communications, 2017)
Reported herein is the gold-catalyzed alkynylation of terminal alkynes using ethynylbenziodoxolones (EBXs), where EBXs serve a dual role as oxidants as well as alkyne transfer agents to access unsymmetrical 1,3-diynes. Hence, the catalytic system requires no external oxidants and is compatible with a broad range of substrates, including those with polar functional groups such as NH, OHand B(OH)(2).

External oxidant-dependent reactivity switch in copper-mediated intramolecular carboamination of alkynes: access to a different class of fluorescent ionic nitrogen-doped polycyclic aromatic hydrocarbons - Shaikh, Aslam C.; Banerjee, Somsuvra; Mule, Ravindra D.; Bera, Saibal; Patil, Nitin T. (Journal of Organic Chemistry, 2019)
An interesting case of external oxidant-controlled reactivity switch leading to a divergent set of ionic nitrogen-doped polycyclic aromatic hydrocarbons (N-doped PAHs), is presented here, which is quite unrecognized in copper-mediated reactions. In the current scenario, from the same pyridino-alkyne substrates, the use of the external oxidant Ph1(0Ac)2, in combination with Cu(OTf)(2), gave N-doped spiro-PAHs via a dearomative 1,2-carboamination process; whereas, without the use of oxidant, an alkyne/azadiene [4 + 2]-cycloaddition cascade occurred to exclusively afford ionic N-doped PAHs. These newly synthesized N-doped PAHs further exhibit tunable emissions, as well as excellent quantum efficiencies.

Enantioselective Au(I)/Au(III) redox catalysis enabled by chiral (P,N)-ligands - Chintawar, Chetan C.; Bhoyare, Vivek W.; Mane, Manoj V.; Patil, Nitin T. (Journal of the American Chemical Society, 2022)
Presented herein is the first report of enantioselective Au(I)/Au(III) redox catalysis, enabled by a newly designed hemilabile chiral (P,N)-ligand (ChetPhos). The potential of this concept has been demonstrated by the development of enantioselective 1,2-oxyarylation and 1,2-aminoarylation of alkenes which provided direct access to the medicinally relevant 3-oxy- and 3-aminochromans (up to 88% yield and 99% ee). DFT studies were carried out to unravel the enantiodetermining step, which revealed that the stronger trans influence of phosphorus allows selective positioning of the substrate in the C-2-symmetric chiral environment present around nitrogen, imparting a high level of enantioselectivity.